Strategies for trading in money markets - Beck, Fabian (Managerial Economics, 2025)
Money market trading is a part of Investment Banking and highly business relevant to the Swiss Banking sector. It is astonishing, therefore, that there are very few scientific studies or papers available on this subject. The goal of this article is to clarify and analyse the relevance, chances, and risks of money market trading within the Swiss banking sector and provides comprehensive information not only to professionals such as employees of banks but also for other clients interested in this specific topic. Various aspects of the money market were analysed, taking in a mix of interviews with experienced banking professionals as well as literary analysis. These aspects include products of and participants in the money market and combine it with the politics of the Swiss National Bank over the last few years. Furthermore, the implications of Basel III on cash trading were explored and explained by way of an example. From the interviews with banking experts, some basic requirements for the job profile of money market traders were defined, 5 strategies for money trading designed and related risks identified.